ANALISIS STABILITAS BANGUNAN PENGENDALI SEDIMEN PADA KONDISI BANJIR RANCANGAN DAN TAMPUNGAN SEDIMEN PENUH : SUATU KASUS DI ARBORETUM SUMBER BRANTAS, KOTA BATU - Andi Setyo Pambudi (Jurnal Teknik Sipil, 2021)
The level of land-use change in the Brantas watershed includes encroachment in the upstream area of the spring which has been increasingly massive since the 1960s, and reached the highest level in the late 1990s which driving the watershed damage. The damage in the upstream area encourages the need to increase resilience by building The Sumber Brantas Arboretum Area. This area is equipped with sedimentary control structures to ensure the long-term sustainability of the arboretum. A recent study of the rainfall plan and the security level of the sedimentary control building to the arboretum became an interesting thing to be reviewed. The analytical approach used in this study is quantitative. The method used for flood design analysis uses three methods including Log Pearson Type III Method, Gumbel Method, and Iwai Method. The selected hydrograph is the Nakayasu Hydrograph. Hydraulics analysis of sediment control buildings using HEC-RAS tools with several other hydrological calculations. The results of the analysis in the Sumber Brantas Arboretum Area showed that the design flood discharge (Q) was 59.35 m3 / sec. In flood design conditions with its own weight, the åf of the sediment control building is 42.2 (higher than the minimum safety level) and it is relatively safe, either in normal or in an earthquake condition. In the design flood conditions with full sediment storage, the Sf of sediment control buildings is 1.6 (higher than the minimum safety level) so that it is relatively safe, either in normal or in an earthquake condition.